PENERAPAN KEGIATAN FINGER PAINTING BAHAN ALAM UNTUK MENINGKATKAN MOTORIK HALUS ANAK USIA 2-4 TAHUN DI TPA AISYIYAH KOTA PROBOLINGGO - Sulasmini Sulasmini; Indriana Warih Windasari (LPPM STAI Muhammadiyah Probolinggo, 2023)
In this study, using classroom action research (Classroom Action Research) the results of which are then outlined in the form of a description (descriptive) or learning research carried out by the teacher with the aim of solving the learning problems faced by the teacher in order to improve and enhance the quality and learning outcomes by trying new things. Researchers found that finger painting or finger painting is very effective for improving fine motor skills in children 2-4 years old, because with finger painting children can trace shapes, understand colors, and are able to give the appropriate color, or in other words, finger painting. this time is beneficial for the growth of children's fine motor skills with the advancement of technological developments that have a negative impact on children's growth, namely the decrease in their fine motor skills. So that researchers consider that research on this matter really needs to be done considering the crucial and so bad impact of technological advances on this decline encourages research